Method and system for testing oxidation resistance of lubricating oil
Through the three-level process of sample pretreatment, multi-field coupling test and extreme strengthening test, the problem that the existing lubricant antioxidant performance testing method cannot accurately simulate complex working conditions is solved, and accurate evaluation and real-time early warning of lubricants under complex working conditions are achieved.
Patent Information
- Application Number
- CN202511059715.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-30
- Publication Date
- 2025-10-03
AI Technical Summary
Existing testing methods for the antioxidant properties of lubricating oils cannot accurately simulate complex and changeable actual operating conditions, ignore the impact of key oxidation products, and the test results are disconnected from actual usage. In addition, the detection efficiency and accuracy are insufficient.
A three-level testing process of sample pretreatment, multi-field coupling test and extreme strengthening test is adopted, including hot and cold cycles, dynamic temperature changes, vibration coordinated processing, alternating introduction of mixed gases, humidity control, photoelectrocatalysis and pressure pulse cycles, etc., combined with the use of microporous structure and tracers to simulate the oxidative environment under complex working conditions.
It significantly shortens the oxidation degradation test cycle, provides richer time node data, can accurately reflect the antioxidant performance of lubricants under complex working conditions, realizes real-time antioxidant performance warning, and improves the accuracy and efficiency of test results.
Smart Images

Figure CN120741830A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lubricating oil testing methods, and in particular to a method and system for testing the anti-oxidation performance of lubricating oil. Background Art
[0002] A lubricant's ability to resist oxidation at room temperature is often referred to as its oxidation stability. Lubricant oxidation at high temperatures is also known as thermal oxidation or thin-layer oxidation. Besides intermediate products such as alcohols, aldehydes, ketones, and acids, the final products are mostly condensation products, such as asphaltenes, coke, and carbon deposits, which form varnishes and solid sediments. Besides increased viscosity affecting lubrication and corrosive effects from acidic components, the varnish and solid deposits formed on metal surfaces can significantly impact mechanical operation. Therefore, anti-oxidation testing is generally required when testing lubricant performance.
[0003] For example, the patent document with patent application number CN202111508188.7 discloses a method for testing the antioxidant properties of lubricating oil and a system for testing the antioxidant properties of lubricating oil. The method mainly involves placing a lubricating oil sample in a closed container under set temperature and pressure conditions, introducing a certain amount of oxygen, and evaluating its antioxidant properties by detecting parameters such as the acid value and viscosity changes of the lubricating oil during the oxidation process. The test system consists of a temperature control device, a pressure regulating device, a gas introduction device, and a parameter detection instrument.
[0004] It can be seen that the above test method has the following obvious shortcomings in actual testing: First, in actual applications, lubricants operate under extremely complex operating conditions. Temperatures fluctuate significantly during equipment startup, operation, and shutdown, and pressures change due to changes in equipment load. Furthermore, the gases they come into contact with may contain not only oxygen but also water vapor and exhaust gases from fuel combustion. Simply setting a fixed temperature and pressure and introducing a single oxygen source cannot simulate real-world scenarios such as the sudden temperature changes caused by frequent starts and stops of automobile engines, the pressure fluctuations caused by high-pressure shocks in industrial hydraulic equipment, or the effects of sulfur-containing exhaust gases on lubricant oxidation. This results in test results that are out of sync with actual usage and fail to accurately reflect the lubricant's antioxidant properties under complex operating conditions.
[0005] Second, the antioxidant performance is evaluated by testing a few parameters such as acid value and viscosity, ignoring the impact of other key oxidation products such as aldehydes and ketones on the performance of lubricants. The parameter detection and analysis in the entire testing process are greatly limited, and the test efficiency and accuracy of the results are difficult to guarantee.
[0006] Based on this, it is necessary to design a lubricating oil antioxidant performance testing method and system that can simulate complex and changeable actual working conditions. Summary of the Invention
[0007] The present invention solves one of the above-mentioned technical problems, and the technical solution adopted is: a method and system for testing the antioxidant performance of lubricating oil, comprising the following steps: sample pretreatment: taking at least two equal amounts of lubricating oil samples, of which at least one is added with a blend of glass fiber powder and ammonium vanadate powder, and then immediately transferring them to a high-temperature environment after being frozen at low temperature to complete a hot and cold cycle.
[0008] The low-temperature freezing temperature is minus 15℃±2℃ and the time is 3h±15min, and the high-temperature environment is 100℃±5℃ and the time is 2h±15min; among them, the number of hot and cold cycles is 4 times, which accelerates the oxidation reaction of the sample under drastic temperature changes and amplifies the difference in antioxidant performance.
[0009] Multi-field coupling test: The lubricating oil sample is injected into the metal cavity, and the temperature dynamic change and vibration are first processed in coordination. Then, mixed gases of different components are alternately introduced at a constant temperature and the humidity cycle is synchronously controlled.
[0010] Multi-field coupling can simulate the complex oxidation environment that lubricants face in actual equipment: dynamic temperature changes accelerate molecular thermal motion to increase the oxidation reaction rate, vibration increases the contact frequency between the lubricant and the cavity surface and promotes the migration of oxidation products, alternating mixed gases (such as oxygen and nitrogen) provide differentiated oxidizing media, and synchronously controlled humidity changes the adsorption characteristics of deposits by affecting interfacial tension. This makes the oxidation reaction more similar to the actual degradation process, prompting the directional formation and accumulation of deposits within the micropores of the metal cavity according to regional characteristics. By reproducing the comprehensive degradation conditions that lubricants may encounter during equipment operation, the test results can directly reflect the anti-oxidation performance of the lubricant under complex operating conditions, resolving the problem that single-factor testing cannot reflect the actual oxidation patterns.
[0011] Secondly, it can enhance the oxidation reaction process: increased temperature reduces the anti-oxidation stability of lubricating oil, vibration accelerates the diffusion and deposition of oxidation products, active gases (such as high-concentration oxygen) provide sufficient oxidants for the oxidation reaction, and humidity control promotes the adsorption of polar oxidation products in micropores, significantly shortening the test cycle of oxidation degradation and better matching the test requirements.
[0012] Due to differences in temperature distribution, gas contact amount, and vibration transmission efficiency in different areas of the metal cavity, an oxidation condition gradient is formed, causing the deposits to exhibit regional accumulation characteristics in the micropores (such as faster deposition in high-temperature areas).
[0013] Compared with single-factor testing, multi-field coupling can advance the onset of significant oxidative degradation and obtain richer time node data (such as 12h, 24h, etc.) within the same test cycle, facilitating the establishment of a more accurate content-time change curve.
[0014] In addition, it should be noted that if the sediment content changes suddenly after a certain parameter (such as humidity) is adjusted, the critical impact threshold of the parameter in the actual equipment can be reversely inferred. For example, if the sediment content of a certain lubricant is found to increase sharply under high humidity, it may be suggested that the replacement cycle of the oil should be shortened in a humid environment.
[0015] Extremely enhanced testing: The samples are first subjected to photoelectrocatalytic treatment using a combination of UV light and an electric field, followed by oxidation treatment using pressure pulse cycles and the introduction of sulfur-containing gases.
[0016] The extreme enhancement test amplifies the oxidative degradation trend of lubricants through a two-stage enhancement mechanism of photoelectrocatalysis and pressure sulfur corrosion: when ultraviolet light and electric field are used in synergistic treatment, ultraviolet light provides energy to photoactivate lubricant molecules, reducing the activation energy of the oxidation reaction, while the electric field directionally migrates polar oxidation products, accelerating their adsorption reaction with the metal cavity surface. The two synergistically enhance the photoelectrocatalytic effect and promote the generation of free radicals and chain oxidation reactions.
[0017] Subsequent pressure pulse cycles and the intervention of sulfur-containing gases destroy the colloidal stability of the lubricating oil through alternating pressure changes, causing suspended oxidation products to aggregate into larger particles. Sulfur-containing gases (such as hydrogen sulfide) act as strong oxidants and react with unsaturated components in the lubricating oil to generate corrosive sulfides, further exacerbating the formation and accumulation of deposits, simulating the accelerated degradation process under extreme working conditions.
[0018] Data evaluation: After the test is completed, the sediment content at different time points is obtained and the critical warning of the lubricant's antioxidant performance is completed.
[0019] This test method simulates the oxidative environment of lubricants under complex working conditions through a three-stage test process of pretreatment, multi-field coupling, and extreme enhancement. It combines dynamic monitoring of sediment content to achieve early warning of antioxidant performance. It comprehensively covers the possible deterioration causes of lubricants and ensures that the test results are consistent with actual usage scenarios.
[0020] Specifically: Sample pretreatment accelerates the oxidation reaction of lubricating oil under sudden temperature changes by adding tracer powder (glass fiber or ammonium vanadate) and hot and cold cycles, thereby amplifying the difference in antioxidant performance; it can specifically accelerate the oxidation process of samples with weaker antioxidant performance, making the difference in sediment generation between different samples more significant, making it easier to quickly distinguish between good and bad performance.
[0021] The multi-field coupling test utilizes the synergistic effects of temperature, vibration, mixed gas, and humidity to simulate the oxidation conditions of multiple factors in actual use, prompting the directional generation of deposits in the micropores of the metal cavity.
[0022] The extreme intensive test further intensifies the oxidation reaction and stimulates the potential deterioration trend of the lubricant through the intervention of photoelectrocatalysis, pressure pulses and sulfur-containing gases.
[0023] Ultimately, by tracking sediment content changes at different time points, critical signals of oxidative degradation are captured, enabling early warning of antioxidant performance. This method allows for real-time assessment of critical antioxidant performance during the test, avoiding the lag associated with traditional methods that require waiting until the test is complete to assess the performance.
[0024] In addition, the addition of tracer powder (such as ammonium vanadate) can be used as a tracer for oxidation reactions. By analyzing the distribution state of powder in the sediment, the flow path and oxidation concentration area of the lubricating oil in a multi-field coupling environment can be reversely inferred, providing clues for the optimization of equipment oil circuit design.
[0025] Based on any of the above technical solutions, further optimization is that: the metal cavity is a titanium alloy cavity with a plurality of microporous structures on the inner wall.
[0026] By constructing a microporous wear surface structure inside the titanium alloy cavity, the surface state of mechanical parts after wear can be simulated, making the test environment closer to actual working conditions and improving the authenticity of the antioxidant performance evaluation.
[0027] This structural design can simulate the actual contact interface between lubricating oil and mechanical parts in actual use. The microporous structure simulates the pits and scratches formed on mechanical parts due to long-term wear, so that the lubricating oil forms an oil film distribution consistent with the actual working conditions during the test, such as oil film retention in the micropores and oil film rupture in the edge area, which solves the problem of dynamic changes in the oil film that cannot be simulated by the smooth inner wall in the existing technology.
[0028] Secondly, the microporous structure increases the contact area between the cavity and the lubricating oil, accelerating the diffusion rate of oxygen, impurities, etc. in the oil film. Its effect is better than the mass transfer method that simply relies on gas introduction, making the oxidation reaction more complete.
[0029] Based on any of the above technical solutions, further optimization is that: the inner wall of the titanium alloy cavity is passivated with a nitric acid solution, and a microporous wear surface structure is formed on the surface of the titanium alloy cavity.
[0030] A dense oxide film is formed on the surface of the titanium alloy through a nitric acid solution passivation treatment in advance. The thickness of the dense oxide film is controlled at 20nm-50nm, which not only prevents the cavity itself from being corroded by the lubricating oil, but also does not interfere with the oxidation reaction of the lubricating oil, thereby ensuring the stability of the test.
[0031] Localized high-temperature zones form within the micropores, promoting preferential oxidation of the lubricant within them. The resulting colloid and asphaltene products are deposited preferentially within the micropores, simulating the carbon deposit formation process in worn areas of actual equipment. This is impossible with existing smooth interior wall testing. By monitoring the composition and content of deposits within the micropores, it also provides early warning of lubricant failure.
[0032] Based on any of the above technical solutions, further optimization is that the added glass fiber powder has a particle size of 5-10 μm, the ammonium vanadate powder has a particle size of 2-5 μm, and the added amount of both powders is 0.5%-1.5% of the mass of the lubricating oil sample.
[0033] Glass fiber powder can be used as a carrier for oxidation reactions. Its fiber structure can absorb oxidation intermediates in the lubricating oil, accelerate the aggregation of deposits, and enhance the mass transfer efficiency within the lubricating oil through the physical stirring effect, making the oxidation reaction more uniform. Due to its smaller particle size, ammonium vanadate powder can penetrate deep into the molecular gaps of lubricating oils, reduce the activation energy of oxidation reactions through catalysis, promote oxidation processes such as peroxide decomposition, and amplify the differences in antioxidant properties between different lubricating oil samples. An addition amount of 0.5%-1.5% can not only ensure the effective promotion of the oxidation reaction, but also avoid abnormal fluctuations in the physical properties of the lubricating oil (such as viscosity) caused by excessive powder, ensuring the relevance of the test environment to the actual usage scenario, thereby enhancing the catalytic effect on the lubricating oil oxidation reaction.
[0034] Based on any of the above technical solutions, further optimization is as follows: first, the specific steps of coordinated processing of dynamic temperature changes and vibration are carried out: the temperature is raised from 50℃±2℃ to 140℃±2℃ at a rate of 6℃ / min±1℃, and a vibration frequency of 80Hz±5Hz is applied simultaneously, and the vibration acceleration is 7g±1g. The above coordinated processing lasts for 3h±20min, and the temperature distribution inside the metal cavity is recorded every 30min during this period.
[0035] Dynamic temperature changes and vibration processing are combined to simulate the real-world degradation environment of lubricant oil during equipment operation through a coupled thermal-mechanical effect. The temperature is raised from 50°C ± 2°C to 140°C ± 2°C at a rate of 6°C / min ± 1°C, gradually increasing the activity of lubricant molecules and accelerating oxidation reactions and deposit formation. Simultaneously applied vibrations of 80Hz ± 5Hz and accelerations of 7g ± 1g enhance the contact frequency and shearing between the lubricant and the metal cavity surface, promoting the migration and deposition of oxidation products into the microporous structure. Based on any of the above technical solutions, a further optimization is provided: The specific steps for alternating the introduction of mixed gases at a constant temperature and simultaneously controlling the humidity cycle are as follows: Maintaining a stable chamber temperature of 100°C ± 2°C, alternately introduce a mixture of oxygen, nitrogen, and carbon dioxide (35%-65% oxygen, 25%-55% nitrogen, and 10%-20% carbon dioxide) (each introduction lasting 45min ± 5min). When switching between components, the pipeline is purged with inert gas for 10min to prevent cross-contamination.
[0036] The humidity cycle was synchronously regulated, with the humidity increasing from 40% RH ± 3% to 85% RH ± 3% at a rate of 8% RH / min, and then decreasing to 40% RH ± 3% at the same rate. One cycle was completed synchronously with the switching of gas components, and this stage lasted for 5h ± 30min.
[0037] Under constant temperature (100℃±2℃), a mixed gas of oxygen, nitrogen and carbon dioxide (the proportion of each component is dynamically adjusted) is introduced alternately and the humidity cycle is synchronously controlled to simulate the oxidative effect of a complex atmospheric environment on lubricating oil through the synergistic effect of "gas component-humidity": oxygen in the mixed gas provides an oxidant for the oxidation reaction, nitrogen acts as an inert medium to adjust the reaction intensity, and carbon dioxide affects the oxidation path by changing the pH of the medium; the synchronous humidity cycle (40%RH±3% to 85%RH±3%) promotes the adsorption and deposition of polar oxidation products in the micropores of the metal cavity by changing the interfacial tension of the lubricating oil, and forms a periodic degradation stimulus synchronously with the switching of gas components, making the oxidation reaction more in line with the dynamically changing degradation conditions in the actual environment.
[0038] Based on any of the above technical solutions, further optimization is as follows: the specific steps for the photoelectrocatalytic treatment of coordinated ultraviolet light and electric field are as follows: the lubricating oil sample that has undergone multi-field coupling testing is retained in a metal cavity, and an ultraviolet light source with a wavelength of 254nm±10nm is turned on so that the light is vertically irradiated on the sample surface, and the light intensity is controlled at 20mW / cm²±5mW / cm²; at the same time, a DC electric field with an intensity of 300V / m±50V / m is applied to the electrodes on both sides of the cavity, and the direction of the electric field is consistent with the direction of ultraviolet light irradiation; the photoelectric coordinated treatment lasts for 1.5h±10min, during which the cavity temperature is kept stable at 80℃±5℃.
[0039] The photoelectrocatalytic treatment that combines ultraviolet light with an electric field strengthens the lubricant oxidation reaction through light activation and electric field acceleration: ultraviolet light with a wavelength of 254nm±10nm provides energy to the lubricant molecules, causing them to undergo photodecomposition to produce free radicals, thereby reducing the activation energy of the oxidation reaction; at the same time, a DC electric field of 300V / m±50V / m on both sides of the cavity (in the same direction as the ultraviolet light) directionally migrates polar free radicals and oxidation products, accelerating their collision and adsorption with the metal cavity surface. The two synergistically enhance the photoelectrocatalytic effect, prompting the rapid generation of oxidation products and their deposition in the micropores.
[0040] Based on any of the above technical solutions, further optimization is as follows: the specific steps of pressure pulse cycle and oxidation treatment with sulfur-containing gas intervention are as follows: after the photoelectrocatalytic treatment is completed, the ultraviolet light source and the electric field are turned off, and a sulfur-containing mixed gas is introduced into the cavity (of which the volume of hydrogen sulfide gas accounts for 2%±0.5%, and the rest is dry air), and the gas flow rate is controlled at 50mL / min±10mL / min; a pressure pulse cycle is performed simultaneously, and the pressure is increased from 0.8MPa±0.1MPa to 3.5MPa±0.2MPa at a rate of 0.2MPa / s, maintained for 30s, and then dropped to the initial pressure at the same rate to complete a pulse cycle, and the cycle period is 5min±30s; this stage lasts for 2h±15min, during which the changes in the concentration of gas components in the cavity are monitored in real time.
[0041] The oxidation treatment with pressure pulse cycle and sulfur-containing gas intervention aggravates the deterioration of lubricating oil through the synergistic effect of pressure disturbance and sulfur corrosion enhancement: hydrogen sulfide in the sulfur-containing mixed gas (hydrogen sulfide accounts for 2%±0.5% by volume) acts as a strong oxidant, reacting with unsaturated hydrocarbons in the lubricating oil to form sulfides, accelerating the formation of oxidation products; the simultaneous pressure pulse cycle (from 0.8MPa±0.1MPa to 3.5MPa±0.2MPa at a rate of 0.2MPa / s, maintaining for 30s and then reducing the pressure) destroys the colloidal stability of the lubricating oil through alternating pressure changes, causing suspended oxidation products to aggregate into larger particles and deposit in the micropores of the metal cavity. The cycle period of 5min±30s and the total duration of 2h±15min form a continuously enhanced degradation environment, simulating the scenario of pressure fluctuations and corrosive gases acting together under extreme working conditions.
[0042] Based on any of the above technical solutions, further optimization is: a specific method for completing the critical warning of the anti-oxidation performance of lubricating oil, including: sample carrier pretreatment: using anhydrous ethanol and ultrasonic cleaning of the titanium alloy cavity, and then placing it in a vacuum drying oven for drying; using an X-ray fluorescence spectrometer to measure the initial elemental composition of the cavity surface, and recording the content of the base metal and oxygen element as the baseline value.
[0043] Eliminate the interference of the titanium alloy cavity's own material on deposit detection, and ensure that the subsequent collected sediment content data only reflects the deposits generated by the lubricating oil in the simulated working condition test, rather than the initial elements on the cavity surface (such as the base metal oxide layer or residual impurities), thereby ensuring the accuracy and pertinence of the sediment content analysis, and providing a reliable benchmark reference for subsequent failure trend warnings based on content changes.
[0044] Sediment collection: 5 different collection points were selected in the titanium alloy cavity; at the 12th, 24th, 48th and 72nd hours of the lubricating oil simulation working condition test, the sediments in the micropores of each of the 5 preset collection points were gently scraped with a probe. After each scraping, the probe surface was purged with inert gas, and the sediments at each point were collected separately into the corresponding numbered quartz boat.
[0045] Among them, point 1 selects micropores in the low-temperature and low-friction zone, point 2 selects micropores in the medium-temperature and slow-friction zone, point 3 selects micropores in the high-temperature and high-load zone, point 4 selects micropores in the local turbulent zone, and point 5 selects micropores in the oil retention zone.
[0046] The sediment collection step involves presetting five differentiated collection points in the titanium alloy cavity (covering typical areas such as low temperature and low friction, high temperature and high load, and oil retention), collecting sediments at four key time nodes (12h, 24h, 48h, and 72h), and using inert gas-purged probes and individually numbered quartz boats to achieve independent separation of samples at each point.
[0047] Its core principle is to capture the generation rate and accumulation characteristics of deposits in different areas by simulating the differences in different local environments within the lubricating oil system under actual working conditions (such as temperature, friction intensity, oil fluidity, etc.), and provide scene-representative samples for subsequent content analysis.
[0048] The five points correspond to typical areas in the lubricating oil system where differences in deposit accumulation are prone to occur. Sediments in each area can be collected separately to avoid averaging errors caused by mixed sampling, accurately reflect the local degradation status, and accurately capture regional differences.
[0049] Through continuous data collection at four time nodes, the dynamic accumulation process of sediments over the test time is recorded, providing continuous data support for establishing content-time change curves and judging failure trends, and dynamically tracking time changes.
[0050] The sediments at each point are collected, numbered and stored separately to ensure that the data at each point are not cross-contaminated during subsequent extraction and content calculation, thereby ensuring the accuracy of the analysis results and ensuring sample independence.
[0051] Through this approach, sediment data at different locations can be directly correlated with the operating conditions of the area in which they are located (for example, data from point 3 in the high-temperature, high-load zone can directly reflect the degree of degradation under extreme conditions), making the content trend more closely linked to actual operating conditions. Independent analysis of each location can not only identify early failure signals in a local area (such as a single location triggering an early warning), but also comprehensively assess the overall system status through multiple locations, avoiding missed or misjudgment and improving the accuracy of warnings.
[0052] The five points cover the main degradation scenarios that may occur in the lubricating oil system, so that the collected data can fully support the simulation analysis of different failure modes (such as gradual deterioration, sudden rise warning, etc.), making the simulation scenarios more comprehensive.
[0053] It also includes, first, if the sediment at a specific point (such as point 3 in the high-temperature and high-load area) increases abnormally, it can be reversely inferred that the area may have potential problems such as local overheating and abnormal friction, providing an indirect basis for troubleshooting system failures.
[0054] Second, by comparing the differences in deposits at different points, the degree of influence of the operating conditions in each area on lubricant degradation (such as the differences between turbulent areas and stagnant areas) can be analyzed, providing data support for optimizing lubricant system design (such as improving the oil flow path).
[0055] Sediment extraction and mass determination: The sediments in five quartz boats were transferred to polytetrafluoroethylene containers respectively, and 10 mL of supercritical CO2 was added to each container. The containers were rinsed under magnetic stirring for 15 min. The operation was repeated twice. After the rinse liquids from each point were combined, they were evaporated to dryness under reduced pressure at 50°C. The total mass of the dried sediments at each point was weighed separately.
[0056] The sediment extraction and mass determination steps utilize the strong solubility and low surface tension properties of supercritical CO2 to perform targeted extraction of sediments at five locations: supercritical CO2 can efficiently dissolve residual components of lubricating oil while avoiding damage to solid sediments. Magnetic stirring, flushing, and repeated operations ensure complete transfer of sediments. Subsequently, the solvent is removed by reduced pressure evaporation and weighed separately to achieve accurate quantification of the mass of sediments at each location. Utilizing the excellent extraction properties of supercritical fluids, the sediments are separated and purified to provide accurate mass data for calculation of content per unit area.
[0057] Advantages include: Sediment Purification and Separation: Supercritical CO2 flushing removes residual undegraded lubricating oil and soluble impurities from the sediment, ensuring that the total weighed mass reflects only the actual solid sediment, reducing interference factors. The efficient extraction capacity of supercritical CO2 and repeated flushing minimizes residual sediment loss. Combined with reduced pressure evaporation and drying, it effectively removes solvents, making the weighing result closer to the true sediment mass.
[0058] Guaranteeing the independence of point data: Samples at five points are extracted and weighed separately to maintain the independence of the data at each point, connecting with the above-mentioned separate collection links to ensure that subsequent analysis can correspond to specific areas.
[0059] Basis for mass quantification: The precise mass of sediment at each point is obtained by weighing after drying, providing core data for calculating the sediment content per unit area (mass / micropore area), which is the numerical basis for subsequent trend analysis and early warning judgment.
[0060] Content calculation and early warning: measure the total area of micropores at 5 sampling points respectively, calculate the sediment content per unit area at each point, and independently draw a curve of content per unit area and time; If the sediment content change at the standard point meets the safety range required by the current lubricant industry standard, it is considered a normal stable change group; otherwise, the current lubricant is determined to be in a critical state. Based on the curve change of the normal stable change group, the maximum curve slope of two consecutive time nodes is determined as the slope threshold, and the maximum increase of the current curve within 24 hours is used as the increase threshold. When the slope of the curve at two consecutive time nodes at a certain point is greater than the set slope threshold, or the increase within 24 hours of the sampling point is greater than the set increase threshold, it is determined that the anti-oxidation performance of the lubricating oil in the point area corresponding to the point has reached the critical warning point; based on the results of the five points, if ≥3 sampling points trigger an alarm, it is determined to be a critical warning for the overall anti-oxidation performance of the lubricating oil.
[0061] The absolute mass of the sediment is converted into content per unit area (eliminating the impact of point area differences), and then through quantitative analysis of the curve slope and single-node amplitude, the critical signals of lubricant degradation in different areas are captured. Finally, the overall system status is judged based on the multi-point results, so that the early warning reflects both local characteristics and overall trends.
[0062] Specifically, by measuring the total area of micropores at each point, the total mass of sediment is converted into content per unit area (mg / mm²), eliminating the interference of differences in micropore size at different points on the data and achieving horizontal comparability of each point and time node.
[0063] The conversion of content per unit area makes the sediment data of the five points comparable under a unified dimension. For example, the content changes in the high-temperature and high-load area (point 3) and the oil retention area (point 5) can be directly compared, clearly showing the degradation differences between different areas.
[0064] Through dual threshold judgment of slope and increase, it can capture both gradual degradation with continuous deterioration (such as the continuous slope exceeding the limit in group 3) and explosive degradation with sudden sudden increase (such as the single node increase exceeding the limit in groups 4 and 5), covering multiple failure modes.
[0065] The rule of integrating the results of multiple points reduces the impact of accidental errors. For example, when a single point triggers an early warning due to local interference, it will not directly determine that the entire system has failed. However, when most points (≥3) are abnormal, the degradation trend of the overall system can be clarified, thereby improving the robustness of the early warning.
[0066] A comprehensive judgment rule for triggering early warning at ≥3 points is set to avoid misjudgment caused by abnormalities in a single area, and at the same time prevent local degradation from being masked by the overall situation, thus realizing graded early warning from local to overall.
[0067] In addition, by recording the time difference and regional distribution of early warning triggers at each point, the diffusion path of lubricant deterioration (such as spreading from high-temperature areas to the surrounding areas) can be reversely inferred, providing data support and basis for tracing the source of failure and optimizing maintenance strategies (such as targeted replacement of lubricants in local areas).
[0068] Among them: The sediment data collected at four time points at point 1 correspond to Figure 1 The sampling values of group 1; the sediment data collected at four time points at point 2, corresponding to Figure 1 The sampling values of group 2; the sediment data collected at four time points at point 3, corresponding to Figure 1 The sampling values of group 3; the sediment data collected at point 4 at four time points, corresponding to Figure 1 The sampling values of group 4; the sediment data collected at point 5 at four time points, corresponding to Figure 1 The sample values of group 5.
[0069] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention selects five different sampling points in the metal cavity for testing, and combines the sediment content data and trend characteristics of four time nodes to comprehensively reflect the differences in the antioxidant performance of the same lubricant in different areas, facilitating a comprehensive assessment of the overall failure trend of the lubricant.
[0070] 2. The present invention triggers an early warning based on the changing trend of the sediment content in different groups, such as when the slope of two consecutive nodes exceeds the limit or the 24-hour increase of a single node exceeds the limit. It can accurately identify the critical early warning state of the lubricating oil's antioxidant performance and provide a reliable basis for timely maintenance measures.
[0071] 3. The present invention simulates a variety of complex working conditions through multi-step testing, including multi-field coupling testing and extreme strengthening testing. It can specifically analyze the antioxidant performance of lubricating oil under the influence of different environmental factors, making the test results more in line with actual application scenarios.
[0072] 4. The data and trend characteristics compiled by the present invention provide a clear basis for comparing and analyzing different scenarios of lubricant failure trend warning, and help provide scientific guidance for the selection of lubricants and the formulation of replacement cycles under different working conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0073] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the following briefly describes the drawings required for the specific embodiments or the description of the prior art. Similar elements or components are generally identified by similar reference numerals throughout the drawings. Elements or components in the drawings are not necessarily drawn to scale.
[0074] Figure 1 Schematic diagram of lubricating oil failure trend characteristic curve corresponding to five groups of sediment content data collected at different time points in an embodiment of the present invention. DETAILED DESCRIPTION
[0075] The following embodiments of the technical solution of the present invention are described in detail with reference to the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention and are therefore only used as examples and are not intended to limit the scope of protection of the present invention. Figure 1 As shown in .
[0076] Example: In this example, for the same lubricating oil sample, five different sampling points were selected in the metal cavity (corresponding to groups 1 to 5, respectively, where the points corresponding to group 1 are standard points), and their antioxidant performance and failure trends were analyzed through multi-step testing.
[0077] 1. Experimental Preparation: Sample and Equipment: 1000 mL of industrial lubricant (industrial gear oil) was injected into a titanium alloy cavity (containing microporous structures) whose inner wall had been passivated with nitric acid. Five sampling points were set within the cavity (top area, middle left area, middle friction pair contact area, bottom corner area, and middle sidewall area). The total micropore area at each point was 100 mm².
[0078] Pretreatment: The cavity was ultrasonically cleaned with anhydrous ethanol for 15 min and dried in vacuum at 60°C. The initial elemental composition of the surface was determined by X-ray fluorescence spectrometry, and the baseline values of titanium and oxygen elements were recorded.
[0079] 2. Test steps: Sample pretreatment: The lubricating oil in the cavity is subjected to four hot and cold cycles (freezing at -15°C for 3 hours and standing at 100°C for 2 hours) to simulate extreme temperature shock.
[0080] Multi-field coupling test: Dynamic temperature change and vibration coordination: Increase the temperature from 50℃±2℃ to 140℃±2℃ at 6℃ / min±1℃, and simultaneously apply 80Hz±5Hz vibration (acceleration 7g±1g) for 3h±20min, and record the temperature distribution at each point every 30min.
[0081] Constant temperature gas and humidity cycle: maintain the chamber temperature at 100℃±2℃, alternately introduce mixed gases (oxygen 35%-65%, nitrogen 25%-55%, carbon dioxide 10%-20%, each time for 45min±5min), and purge the pipeline with inert gas for 10min when switching; simultaneously control the humidity (40%RH±3%, 85%RH±3%, 40%RH±3%, rate 8%RH / min), with a total duration of 5h±30min.
[0082] Extreme Intensification Test: Photoelectrocatalytic Treatment: Irradiate the sample perpendicularly to the surface with a 254nm±10nm UV light source (20mW / cm²±5mW / cm²) while applying a 300V / m±50V / m DC electric field (aligned with the direction of the light) at 80°C±5°C for 1.5h±10min.
[0083] Pressure sulfur etching treatment: turn off the light source and electric field, introduce a mixed gas containing 2%±0.5% hydrogen sulfide (flow rate 50mL / min±10mL / min), and simultaneously perform pressure pulse cycles (0.8MPa±0.1MPa, 3.5MPa±0.2MPa, cycle 5min±30s) for 2h±15min, and monitor the gas composition in real time.
[0084] 3. Sediment collection and analysis: Collection and extraction: At the test time points of 12h, 24h, 48h, and 72h, the sediments at five locations were scraped with a probe. After flushing with supercritical CO2 and evaporation at 50°C under reduced pressure, the mass of the dry sediment at each location was weighed.
[0085] Data calculation: Based on the total area of micropores at each point, calculate the sediment content per unit area (mg / mm²). The results are as follows: Top area (Group 1): 12h is 0.08, 24h is 0.12, 48h is 0.17, 72h is 0.21, the trend is normal and stable change, and it has not reached the warning level, so Group 1 can be regarded as a normal and stable change group.
[0086] The slope threshold was set based on the change in sediment content in the top area (Group 1), and the slope of the curve for each 24-h time period was calculated: the slope from 12h to 24h was (0.12-0.08) / 24≈0.0017mg / (mm²・h), the slope from 24h to 48h was (0.17-0.12) / 24≈0.0021mg / (mm²・h), and the slope from 48h to 72h was (0.21-0.17) / 24≈0.0017mg / (mm²・h). The maximum slope of 0.0021mg / (mm²・h) was taken as the slope threshold.
[0087] The middle left area (Group 2): 12h is 0.09, 24h is 0.15, 48h is 0.24, and 72h is 0.36. The trend is slowly approaching the warning level, and the slope rises in the later period.
[0088] Middle friction pair contact area (Group 3): 0.07 at 12h, 0.13 at 24h, 0.25 at 48h, and 0.42 at 72h. The trend is that the slope of two consecutive nodes exceeds the limit, triggering an early warning.
[0089] The bottom corner area (Group 4) showed a 12-hour increase of 0.10, a 24-hour increase of 0.16, a 48-hour increase of 0.38, and a 72-hour increase of 0.45. This trend indicates that a single node exceeded the 24-hour increase limit, triggering an alert. Within the 24-hour period from 24 to 48 hours, the sediment content in Group 4 increased from 0.16 mg / mm² to 0.38 mg / mm², an increase of 0.22 mg / mm². This exceeded the 0.05 mg / mm² increase threshold set for Group 1, triggering an alert.
[0090] The middle area of the side wall (Group 5): 0.06 at 12h, 0.09 at 24h, 0.12 at 48h, and 0.35 at 72h. The trend is stable in the early stage and a sudden rise warning in the later stage.
[0091] 4. Result determination: Among the five points, three points in Group 3, Group 4, and Group 5 triggered warnings, indicating that the overall antioxidant performance of the lubricant has reached a critical warning state, and the replacement cycle needs to be shortened in actual application.
[0092] This example clearly presents the degradation differences of the same lubricant in different areas through multi-scenario testing, providing a quantitative basis for evaluating its antioxidant performance.
[0093] In summary, this lubricant antioxidant performance testing method, through the synergistic effect of multi-field coupling and extreme enhancement, can accurately capture the degradation differences of the same lubricant in different cavity areas. Deposit data from five locations shows that the top region (Group 1) remains stable, while the middle friction pair contact area (Group 3), the bottom corner area (Group 4), and the middle sidewall area (Group 5) trigger warnings due to the combined influence of temperature, vibration, gas, and pressure. This is consistent with the different trend characteristics presented in the table.
[0094] This test method can not only fully reflect the actual performance of lubricants under complex working conditions, but also provide the specific data and trend characteristics of each point (see Figure 1 The lubricant failure trend characteristic curve corresponding to the sediment content data collected at five different time points in the ) provides a reliable basis for judging the critical warning state of the overall antioxidant performance of the lubricant, and also provides a scientific reference for adjusting the lubricant replacement cycle and equipment maintenance in actual applications.
[0095] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments can still be modified, or some or all of the technical features therein can be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention. For those skilled in the art, any replacement improvements or changes made to the implementation methods of the present invention fall within the scope of protection of the present invention.
[0096] Any matters not described in detail in the present invention are well-known technologies to those skilled in the art.
Claims
1. A method and system for testing the antioxidant properties of lubricating oil, characterized in that: The steps include: Sample pretreatment: Take at least two equal amounts of lubricating oil samples, of which at least one is added with a blend of glass fiber powder and ammonium vanadate powder. After freezing at low temperature, immediately transfer to a high temperature environment to complete the hot and cold cycle; Multi-field coupling test: Lubricant samples are injected into a metal cavity, where they are first subjected to dynamic temperature changes and vibration. Then, mixed gases of different components are alternately introduced at a constant temperature while simultaneously controlling the humidity cycle. Extreme intensive testing: The sample is first subjected to photoelectrocatalytic treatment using a combination of UV light and an electric field, followed by oxidation treatment using pressure pulse cycles and the introduction of sulfur-containing gases. Data evaluation: After the test is completed, the sediment content at different time points is obtained and the critical warning of the lubricant's antioxidant performance is completed.
2. A method and system for testing the anti-oxidation performance of lubricating oil according to claim 1, characterized in that: The metal cavity is a titanium alloy cavity with a plurality of microporous structures on the inner wall.
3. A method and system for testing the anti-oxidation performance of lubricating oil according to claim 2, characterized in that: in, The inner wall of the titanium alloy cavity is passivated by a nitric acid solution, and a microporous wear surface structure is formed on the surface of the titanium alloy cavity.
4. A method and system for testing the anti-oxidation performance of lubricating oil according to claim 3, characterized in that: The added glass fiber powder has a particle size of 5-10 μm, the ammonium vanadate powder has a particle size of 2-5 μm, and the addition amount of both powders is 0.5%-1.5% of the mass of the lubricating oil sample.
5. A method and system for testing the anti-oxidation performance of lubricating oil according to claim 4, characterized in that: First, the specific steps of coordinated treatment of dynamic temperature change and vibration are carried out: the temperature is increased from 50℃±2℃ to 140℃±2℃ at a rate of 6℃ / min±1℃, and a vibration frequency of 80Hz±5Hz and a vibration acceleration of 7g±1g are applied simultaneously. The above coordinated treatment lasts for 3h±20min.
6. A method and system for testing the anti-oxidation performance of lubricating oil according to claim 5, characterized in that: in, The specific steps of alternately introducing mixed gases of different components at a constant temperature and synchronously controlling the humidity cycle are as follows: maintaining the chamber temperature stable at 100°C ± 2°C, alternately introducing a mixed gas consisting of oxygen, nitrogen, and carbon dioxide, with oxygen accounting for 35%-65%, nitrogen accounting for 25%-55%, and carbon dioxide accounting for 10%-20%. When switching components, purge the pipeline with inert gas for 10 minutes to avoid cross contamination; The humidity cycle was synchronously regulated, with the humidity increasing from 40% RH ± 3% to 85% RH ± 3% at a rate of 8% RH / min, and then decreasing to 40% RH ± 3% at the same rate. One cycle was completed synchronously with the switching of gas components, and this stage lasted for 5h ± 30min.
7. A method and system for testing the anti-oxidation performance of lubricating oil according to claim 6, characterized in that: The specific steps for the photoelectrocatalytic treatment using UV light and electric fields are as follows: A lubricating oil sample that has undergone multi-field coupling testing is retained in a metal cavity. A UV light source is turned on, irradiating the sample surface perpendicularly. Simultaneously, a DC electric field is applied to electrodes on both sides of the cavity, with the direction of the electric field aligned with the direction of the UV light. The photoelectric co-processing lasts for 1.5h±10min, during which the cavity temperature is kept stable at 80℃±5℃.
8. A method and system for testing the anti-oxidation performance of lubricating oil according to claim 7, characterized in that: The specific steps for the oxidation treatment with pressure pulse circulation and sulfur-containing gas intervention are as follows: after the photoelectrocatalytic treatment is completed, the ultraviolet light source and the electric field are turned off, and a sulfur-containing mixed gas is introduced into the cavity; the pressure pulse circulation is carried out simultaneously, with a cycle period of 5min±30s; this stage lasts for 2h±15min, during which the changes in the concentration of gas components in the cavity are monitored in real time.
9. A method and system for testing the anti-oxidation performance of lubricating oil according to claim 8, characterized in that: The specific method for completing the critical early warning of lubricant anti-oxidation performance includes: The titanium alloy cavity was cleaned with anhydrous ethanol and ultrasonically cleaned, and then dried in a vacuum drying oven. The initial elemental composition of the cavity surface was measured using an X-ray fluorescence spectrometer, and the content of the base metal and oxygen was recorded as the baseline value. Five different collection points were selected in the titanium alloy cavity. At the 12th, 24th, 48th, and 72nd hour of the lubricating oil simulation test, the sediments in the micropores of each of the five preset collection points were gently scraped with a probe. After each scraping, the probe surface was purged with inert gas, and the sediments at each point were collected separately into a corresponding numbered quartz boat. The sediments in the five quartz boats were transferred to polytetrafluoroethylene containers, and 10 mL of supercritical CO2 was added to each container. The container was rinsed for 15 min under magnetic stirring. The operation was repeated twice. After the rinse liquids at each point were combined, they were evaporated to dryness under reduced pressure at 50°C. The total mass of the dried sediment at each point was weighed separately. Content calculation and early warning: measure the total area of micropores at 5 sampling points respectively, calculate the sediment content per unit area at each point, and independently draw a curve of content per unit area and time; When the slope of the curve at two consecutive time nodes at a certain point is greater than the set slope threshold, or the increase within 24 hours of the sampling point is greater than the set increase threshold, it is determined that the anti-oxidation performance of the lubricating oil in the point area corresponding to the point has reached the critical warning point; based on the results of the five points, if ≥3 sampling points trigger an alarm, it is determined to be a critical warning for the overall anti-oxidation performance of the lubricating oil.
10. A lubricating oil antioxidant performance testing system, characterized in that: The system uses the method according to any one of claims 1 to 9 to test the anti-oxidation performance of lubricating oil.
Citation Information
Patent Citations
Lubricating oil oxidation resistance testing method and lubricating oil oxidation resistance testing system
CN114113551A